2020
DOI: 10.1038/s41377-020-00417-1
|View full text |Cite
|
Sign up to set email alerts
|

Tailored optical propulsion forces for controlled transport of resonant gold nanoparticles and associated thermal convective fluid flows

Abstract: Noble metal nanoparticles illuminated at their plasmonic resonance wavelength turn into heat nanosources. This phenomenon has prompted the development of numerous applications in science and technology. Simultaneous optical manipulation of such resonant nanoparticles could certainly extend the functionality and potential applications of optothermal tools. In this article, we experimentally demonstrate optical transport of single and multiple resonant nanoparticles (colloidal gold spheres of radius 200 nm) dire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 40 publications
0
17
0
Order By: Relevance
“…However, when the laser power increases, the optical force can be dominating, indicating that the trapping force cannot be improved by simply increasing the optical power. Moreover, thermofluidic phenomena may appear at high temperature, e.g., strong natural convection 137 or Marangoni convection, 138 which may also dominate over the thermophoretic effect. A clear power dependency is expected, and the improvement of D T through environmental design is important to improve the optothermophoretic force.…”
Section: Perspectivementioning
confidence: 99%
See 1 more Smart Citation
“…However, when the laser power increases, the optical force can be dominating, indicating that the trapping force cannot be improved by simply increasing the optical power. Moreover, thermofluidic phenomena may appear at high temperature, e.g., strong natural convection 137 or Marangoni convection, 138 which may also dominate over the thermophoretic effect. A clear power dependency is expected, and the improvement of D T through environmental design is important to improve the optothermophoretic force.…”
Section: Perspectivementioning
confidence: 99%
“…Moreover, thermofluidic phenomena may appear at high temperature, e.g. , strong natural convection or Marangoni convection, which may also dominate over the thermophoretic effect. A clear power dependency is expected, and the improvement of D T through environmental design is important to improve the opto-thermophoretic force.…”
Section: Perspectivementioning
confidence: 99%
“…[249][250][251][252][253] There is no doubt that new developments in structured light beams will continuously boost the fields of optical manipulation. 254 Moreover, among the diverse optical trapping schemes discussed in this review, in our view, several topics have great potential to find exciting future applications, such as the optical trapping of metal particles [183][184][185][186][187][188][189] and chiral particles, 52,53 vacuum levitation, structured light in waveguides, [255][256][257][258][259] optical binding and other collective motions in structured light fields, 113,185,[260][261][262] quantum optomechanics, 30 and optical trapping for multidisciplinary applications. 32 In the future, besides SLMs and DMDs, more flexible, efficient and much less expensive devices will be developed to produce structured beams, which can help build the next generation of optical trapping technology.…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, for strong phase gradients, the symmetry of the interaction between two nanoparticles breaks, resulting in a change of the distance, for which stable binding can be achieved. More recently, Rodrigo et al 188 studied how to control the speed of metal nanoparticles by tailored phase-gradient propulsion force. Figures 37(c) and 37(d) show two ring vortex traps with a uniform phase gradient and a tailored nonuniform phase gradient, respectively.…”
Section: Optical Trapping and Transporting Of Metal Nanoparticlesmentioning
confidence: 99%
“…The spinel-type ferrites (MFe 2 O 4 ), where M represents the divalent metal cation, were mainly applied to the fields of magnetic resonance image (MRI) and drug delivery in the earlier study due to their unique magnetic properties [18][19][20]. Interestingly, the recent studies revealed that MFe 2 O 4 has high catalytic performance.…”
Section: Introductionmentioning
confidence: 99%